Analisis Penegakan Hukum Pelaku Penangkapan Ilegal Badak Jawa dan Upaya Pengelolaan Taman Nasional Ujung Kulon - Patonah, Siti Sulaemah Cunayah, Imelda Zahrotunnisa, Patonah (Universitas Sultan Ageng Tirtayasa, 2024)
ABSTRACTThe Javan rhino, also known as Rhinoceros sondaicus, is a protected species under the Minister of Environment and Forestry Regulation No. 106 of 2018 concerning Protected Plant and Animal Types. The Javan rhino population is currently mainly located in Ujung Kulon National Park (TNUK). According to the International Union for Conservation of Nature (IUCN), the Javan rhino has been declared in the Critically Endangered category, which indicates a level of risk approaching extinction in its natural habitat. The Javan rhino faces serious threats due to poaching which has caused a significant decline in its population. This research highlights the Javan rhino poaching incident in Ujung Kulon National Park (TNUK) which occurred in August 2023. Collaboration between the TNUK Center, the police and the Ministry of Environment and Forestry succeeded in identifying six perpetrators through camera traps. To date, the six perpetrators have not been punished due to requests from the public for a postponement of detention. This case shows the seriousness of illegal hunting of the Javan Rhino which has long threatened the Javan Rhino population. Even though regulations have been issued, such as Law Number 5 of 1990 concerning Conservation of Biological Natural Resources and Ecosystems, as well as Pandeglang Regency Regional Regulation No. 2 of 2013 concerning Management of Ujung Kulon National Park, illegal fishing still continues. The research method used in this research is normative legal research with qualitative juridical analysis of legal materials. The results show that the implementation of Pandeglang Regency Regional Regulation No. 2 of 2013 concerning Management of Ujung Kulon National Park has not been implemented optimally, especially in terms of law enforcement for perpetrators of illegal arrests. However, the local community and government continue to strive to maintain the Javan rhino population TNUK.Keywords: Javan Rhinoceros, Illegal Capture, Conservation. ABSTRAKBadak Jawa, yang juga dikenal sebagai Rhinoceros sondaicus, termasuk dalam spesies yang dilindungi berdasarkan Peraturan Menteri Lingkungan Hidup dan Kehutanan No. 106 Tahun 2018 mengenai Jenis Tumbuhan dan Satwa Dilindungi. Populasi badak Jawa saat ini utamanya berada di Taman Nasional Ujung Kulon (TNUK). Menurut International Union for Conservation of Nature (IUCN), badak Jawa telah dinyatakan dalam kategori Kritis (Critically Endangered), yang mengindikasikan tingkat risiko mendekati kepunahan di habitat alaminya. Badak Jawa menghadapi ancaman serius akibat perburuan liar yang menyebabkan penurunan populasi secara signifikan. Penelitian ini menyoroti insiden perburuan badak Jawa di Taman Nasional Ujung Kulon (TNUK) yang terjadi pada Bulan Agustus 2023. Kolaborasi antara Balai TNUK, polisi, dan Kementerian Lingkungan Hidup dan Kehutanan berhasil mengidentifikasi enam pelaku melalui kamera trap. Hingga saat ini, keenam pelaku belum dihukum karena permintaan penundaan penahanan dari masyarakat. Kasus tersebut menunjukkan seriusnya perburuan ilegal terhadap Badak Jawa yang telah lama mengancam populasi Badak Jawa. Meskipun peraturan telah dikeluarkan, seperti Undang-Undang Nomor 5 Tahun 1990 tentang Konservasi Sumber Daya Alam Hayati dan Ekosistemnya, serta Peraturan Daerah Kabupaten Pandeglang No. 2 Tahun 2013 tentang Pengelolaan Taman Nasional Ujung Kulon, penangkapan illegal masih terus ada. Metode penelitian yang digunakan dalam penelitian ini adalah penelitian hukum normatif dengan analisis bahan hukum yang dilakukan secara yuridis kualitatif. Hasilnya menunjukkan bahwa implementasi Peraturan Daerah Kabupaten Pandeglang No. 2 Tahun 2013 tentang Pengelolaan Taman Nasional Ujung Kulon belum dilaksanakan secara maksimal terutama dalam hal penegakan hukum bagi pelaku penangkapan illegal. Meski demikian, masyarakat dan pemerintah setempat terus berupaya menjaga populasi badak jawa di TNUK. Kata Kunci : Badak Jawa, Penangkapan Ilegal, Konservasi.